Expert consensus on management of dermatophytosis in elderly patients, patients with comorbidities, and immunocompromised status: an Indian perspective - Thomas, Jayakar; Parthasaradhi, Anchala; Bajaj, A. K.; Girdhar, Mukesh; Ghoshal, Asok; Haq, Rizwan; Sachdev, Maleeka; Ganjoo, Anil; Kar, Bikash R. (International Journal of Research in Dermatology, 2020)
Dermatophytosis is a common fungal infection of skin contributing to increasing disease burden worldwide. Increasing age, presence of comorbid conditions and immunity have a profound impact on the manifestation of dermatophyte infections. Treatment of dermatophytosis includes monotherapy, combination therapy, or sequential therapy of antifungal drugs. However, specific patient populations such as the elderly, people with comorbid conditions, immunocompromised patients, etc. are subjected to inappropriate adverse events due to highly interacting host and drug factors. Thus, the management of dermatophytosis in special populations is a challenge, and it demands a change in the regular treatment plan. A group of Indian experts reviewed the evidence available on different antifungal agents for the management of dermatophytosis and provided their expert opinion on safe and effective management of the condition in special clinical scenarios. This article summarizes the consensus clinical viewpoint of the entire expert panel for a choice of the antifungal drug, factors to be assessed, and treatment considerations in special populations with dermatophytosis. The panel emphasized that complete knowledge of patient’s clinical history, presence of comorbid conditions, and pharmacokinetic and pharmacodynamic characteristics of antifungal agents and associated potential drug interactions are essential for the successful management of dermatophytosis in these patients. Also, regular monitoring of drug toxicity is important during antifungal therapy in special population.